2020
DOI: 10.3390/cells9051121
|View full text |Cite
|
Sign up to set email alerts
|

Organoids of Human Endometrium: A Powerful In Vitro Model for the Endometrium-Embryo Cross-Talk at the Implantation Site

Abstract: Embryo implantation has been defined as the “black box” of human reproduction. Most of the knowledge on mechanisms underlining this process derives from animal models, but they cannot always be translated to humans. Therefore, the development of an in vitro/ex vivo model recapitulating as closely and precisely as possible the fundamental functional features of the human endometrial tissue is very much desirable. Here, we have validated endometrial organoids as a suitable 3D-model to studying epithelial endomet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 44 publications
0
33
0
Order By: Relevance
“…Here we report on the development of endometrial assembloids, consisting of gland-like organoids surrounded by a matrix rich in primary EnSC, as novel model to parse the cellular dynamics that govern embryo implantation in cycling human endometrium. While assembloids complement and advance other recently described endometrial organoid models (Boretto et al, 2017, Cheung et al, 2021, Fitzgerald et al, 2019, Luddi et al, 2020, Turco et al, 2017, they still lack the cellular complexity of native endometrium, including uNK cells, macrophages and vascular cells. Nevertheless, we demonstrated that aspects of pathological implantation events can be recapitulated in assembloids, rendering them useful as novel models to study mechanisms of reproductive failure and to evaluate potential therapeutic interventions.…”
Section: Discussionmentioning
confidence: 95%
“…Here we report on the development of endometrial assembloids, consisting of gland-like organoids surrounded by a matrix rich in primary EnSC, as novel model to parse the cellular dynamics that govern embryo implantation in cycling human endometrium. While assembloids complement and advance other recently described endometrial organoid models (Boretto et al, 2017, Cheung et al, 2021, Fitzgerald et al, 2019, Luddi et al, 2020, Turco et al, 2017, they still lack the cellular complexity of native endometrium, including uNK cells, macrophages and vascular cells. Nevertheless, we demonstrated that aspects of pathological implantation events can be recapitulated in assembloids, rendering them useful as novel models to study mechanisms of reproductive failure and to evaluate potential therapeutic interventions.…”
Section: Discussionmentioning
confidence: 95%
“…Currently, endometrial organoids are being used to investigate physiological changes during the normal cycle 5 , and pathological endometrial dysfunction in endometriosis, endometrial cancer and other gynaecological conditions 2 . Implantation of the transferred embryo is a rate-limiting step in Assisted Reproductive Techniques (ART) 27 , and organoids are enabling exploration of the molecular mechanisms underpinning implantation 4 . Our technique will enable patients undergoing fertility treatments to have their endometrial function assessed non-invasively prior to initiating a treatment cycle, allowing the hormonal regime and timing of treatment to be tailored accordingly.…”
Section: Discussionmentioning
confidence: 99%
“…We, and others, have previously shown that endometrial organoids provide a valuable model for investigating maternalfetal interactions during early pregnancy, and for exploring the pathophysiology of gynaecological complications such as endometriosis and endometrial cancer [2][3][4][5] . To date, the organoids have been derived from biopsy samples, which, while reproducible and robust, necessitate an invasive procedure performed by a trained clinician.…”
mentioning
confidence: 99%
“…By exposure to a specific hormone treatment protocol encompassing E2 and progesterone (P4), organoids mimicked the full menstrual cycle as well as incipient decidualization (Table 1 and Supplementary Table 3). The robustness of the endometrial organoid platform has been validated by IHC, electron microscopy, array Comparative Genomic Hybridization (aCGH) and transcriptome analysis and, in addition, ion channel functionality and ciliogenesis was demonstrated using these organoid systems (Fitzgerald et al, 2019;Haider et al, 2019;Hennes et al, 2019;Cochrane et al, 2020;Bui et al, 2020;Luddi et al, 2020;Syed et al, 2020). Two groups achieved to derive organoids from trophoblasts, offering the appealing possibility to study trophoblast-endometrium crosstalk in vitro (Haider et al, 2018;Turco et al, 2018).…”
Section: Endometrium Healthy Endometriummentioning
confidence: 99%